Accountants as gatekeepers of financial integrity - a Malaysian perspective - Ida Shafinaz Mohamed Kamil; Sharija Che Shaari; Junaidah Zeno (Faculty of Business, Economics & Accountancy, UMS, 2024)
Accountants play a pivotal role in upholding the integrity of financial systems, particularly as gatekeepers of financial reporting. In Malaysia, the legal framework governing the accounting profession is multifaceted, encompassing various statutes, regulatory bodies, and case law that together ensure the accountability and transparency of financial practices. Employing the doctrinal approach, this paper examines the role of accountants as gatekeepers of financial integrity within the Malaysian legal framework, with a focus on the key legislative provisions, regulatory guidelines, and judicial decisions that shape their duties and responsibilities. The analysis emphasizes the significance of professional ethics, corporate governance, and legal accountability in safeguarding the interests of stakeholders. This paper highlights the legal and ethical challenges accountants face in maintaining financial integrity. The paper concludes by exploring the evolving role of accountants in the face of emerging regulatory changes and technological advancements, and the implications of these shifts for the future of financial governance in Malaysia.